Fine Arts: 5. The Iaşi School of Painting - Between Myth and Reality - Ștefănescu Mirela (Sciendo, 2018)
This paper analyzes a phrase which is specific of cultural space from Iași called "The Iași School of Painting", a term which, as art critics say, is distinguished by several features including the harmony of the composition, the chromaticism and refinement of artistic expression. So, we start in this study with the founders of the first institution of artistic education in Iasi, which strongly influenced the local creative style of plastic expression, then, we talk about the period in which was materialized fully the traditional way of the Iasi school of painting. After December 1989 the visual art from Iasi has gone through many changes, being outlined a new approach to the artistic phenomenon in the context of technological development and the globalization, the moment in which the visual artists tried new plastics formulas. Today the expression the Iasi School of Painting is only a metaphor which illustrates the connection with the glorious past of the great masters.